The Mac OS X Panther Book - Ihnatko Andy (Wiley, 2004)
Developed in cooperation with Apple Computer and written by Mac personality Andy Ihnatko, this book provides entertaining, real-world tips and techniques for getting the most out of Mac OS X Panther